A simple method of evaluating non-isothermal crystallization kinetics in multicomponent polymer systems. (October 2015) - Kratochvíl, Jaroslav; Kelnar, Ivan
Abstract: A new simple method of evaluating non-isothermal crystallization kinetics is proposed. The procedure based on mathematical treatment of DSC cumulative crystallization curves at their inflection point provides three kinetic parameters: temperature of start of crystallization ( T s ), temperature of maximum crystallization rate ( T i ) and numerical value of the maximum crystallization rate ( s i ), and also final crystallinity after cooling ( CR c ). The method is demonstrated on the system poly(ɛ-caprolactone)/poly(lactic acid)/clay C15 and related microfibrillar composite. The method provides the values of T s and T i with standard deviation σ  = 0.3 and 0.4 °C, respectively. The coefficient of variation v of s i and CR c is 5.8 and 1.5%, respectively. The proposed method does not refer to any crystallization model and does not require exact determination of the starting time. It is particularly useful for characterizing a series of samples derived by modification of the neat polymer.